Serum-Free Suspension Culture of the Aedes albopictus C6/36 Cell Line for Chimeric Orthoflavivirus Vaccine Production - Joshua S. Dawurung; Jessica J. Harrison; Naphak Modhiran; Roy A. Hall; Jody Hobson-Peters; Henry de Malmanche (Viruses)
Chimeric orthoflaviviruses derived from the insect-specific Binjari virus (BinJV) offer a promising basis for safe orthoflavivirus vaccines. However, these vaccines have so far only been produced using adherent C6/36 Aedes albopictus mosquito cell cultures grown in serum-supplemented media, limiting their scalable manufacture. To address this, we adapted C6/36 cells for serum-free suspension culture using Sf900-III medium, achieving high peak cell densities (up to 2.5 × 107 cells/mL). Higher agitation rates reduced cell aggregation, and cryopreservation and direct-to-suspension revival were successful, confirming the adapted line’s stability for research and industrial applications. Despite this, BinJV-based chimeric orthoflaviviruses, including BinJV/WNVKUN, a candidate vaccine for West Nile virus, and similar vaccines (BinJV/DENV2 and BinJV/JEVNSW22) for dengue 2 virus and Japanese encephalitis virus, respectively, exhibited substantially reduced titres in C6/36 cultures infected in Sf900-III, a phenomenon attributed to the medium’s acidic pH. Switching to the more alkaline, serum-free CD-FortiCHO medium enhanced the replication of these chimeric viruses to peak titres between 1.7 × 107 and 7.6 × 109 infectious units per mL whilst preserving viral integrity. These findings suggest that suspension-adapted C6/36 cultures in CD-FortiCHO medium can support high-yield vaccine production for various orthoflaviviruses and highlight the important role of cell culture media pH for orthoflavivirus bioprocessing. This scalable mosquito cell-based system could reduce production costs and improve vaccine accessibility, supporting efforts to combat arbovirus-related public health challenges.